Abenomics, Diplomasi Ekonomi, dan Ekspor Infrastruktur Jepang di Indonesia - Aulia, Nurul; Kumala, Lucyana (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
The export of infrastructure from Japan under Shinzo Abe's leadership has been the subject of several studies. Nevertheless, previous research has not extensively examined the Japanese export infrastructure initiatives in Indonesia from the perspective of economic diplomacy analysis. The researchers employed qualitative methodologies by utilizing a case study technique. The data sources utilized in this study encompass both primary and secondary sources. The study employed the theoretical framework of Maiike Okano-Heijman's Economic Diplomacy, which encompasses three primary components: commercial diplomacy, trade diplomacy, and economic/development assistance. These pillars were utilized to evaluate a specific case study.